Aripiprazole: A Case for Side Effect Awareness - Mario Lepore (BJPsych Open)
Aims: Aripiprazole, an atypical antipsychotic, is commonly prescribed for various psychiatric conditions including schizophrenia and bipolar disorder. It is generally considered to have a more favourable side effect profile compared with other antipsychotics, with a lower risk of metabolic side effects and hyperprolactinemia. We present the case of a 57-year-old male who developed marked hypersexuality and excessive spending following the initiation of oral aripiprazole.